Farm field monitoring and irrigation automation using IOT - Vinoth, M; Vithiya, G (International Journal of Engineering and Technology, 2018)
The Agricultural farming crops are produced in low qualitydue to lack of knowledge of farmers and crops destroyed by insects. To overcome that, many implemented factors are used. The factors can be temperature,soil,humidity,etc.,In biotechnology,some techniques are used withthe help of IoT. It is mainly used to increase the crops productivity in good quality.Existing related research works on sensor cloud have primarily focused on the challenges that wireless sensor network (WSN)-based applications. A direct estimate of water use by subsurface measurements of soil water content has been limited by the high cost of reliable soil moisture sensors. Using some sensors and techniques water can be irrigated automatically.IOT plays a vital role in smart farming.By using set of specified sensors,the irrigation man-agement can be done properly.The sensed data from the sensors and the irrigation controller are interfaced with Wi-Fi connection. In naive Bayes, by using decision making process the farmer can decide when and where to irrigate with the help of mobile application. An algo-rithm was developed with threshold values of temperature and soil moisture that was programmed into a microcontroller-based gateway to control water quantity.Â Â
Keywords: IOT; Naïve; Sensors; WSN.